Experimental study of train-induced vibration in over-track buildings in a metro depot. (1st November 2019) - Tao, Ziyu; Wang, Yimin; Sanayei, Masoud; Moore, James A.; Zou, Chao
Highlights: Frequent train operation under over-track buildings may compromise residents comfort. Vibration and noise levels of over-track buildings were compared with standards. Track switches in the throat area can result in impacts transmitting high vibration. Transfer structure helps reducing vibration levels within the low-rise building. Abstract: Over-track buildings in Chinese metro depots have recently been designed to accommodate the rapid urbanization and massive construction of urban rail transit systems. However, train-induced vibration and noise impacts in over-track buildings need to be carefully assessed to provide comfortable working or living environments for the building's occupants. Vibration and noise measurements were carried out in a typical 28-story load-bearing wall supported residence and a 4-story steel-framed office building during train pass-by events in the Qianhai metro depot in Shenzhen, China. Measured points were set at ground level adjacent to the building support structures as well as on upper floors. Train induced noise levels were within both FTA and Chinese limits. Floor vibration levels in the low-rise building were within FTA limit but not the more stringent Chinese limit. Ground-borne vibration signals in the throat area contained high level, short duration impacts generated as cars passed over discontinuities in rails at a switch. Ground vibration levels near the columns under the low-rise building were significantly greater than at the load bearing walls of the high-rise building by 20 dB or more. Levels within the buildings near columns or walls were only 5 dB higher in the low-rise building. The low-rise building transfer structure apparently significantly reduced transmission into the building above the platform. Vertically aligned load bearing walls in the high-rise building more effectively transmitted vibration. The measured vibration reduction from floor to floor was meaningfully less than recommendations in FTA guidelines. This research enriches the database of train-induced vibration and noise in over-track buildings, provides insights into the vibration transmission process into and within over-track buildings and is of value for the design and construction for similar over-track buildings in future train depots.